A comparative analytical assessment of iodides in healthy and pathological human thyroids based on IC-PAD method preceded by microwave digestion - Błażewicz, Anna; Orlicz-Szczęsna, Grażyna; Szczęsny, Piotr; Prystupa, Andrzej; Grzywa-Celińska, Anna; Trojnar, Marcin (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
The aim of the study was to examine correlations between the content of iodides in 66 nodular goiters and 100 healthy human thyroid tissues (50- frozen and 50 formalin-fixed). A fast, accurate and precise ion chromatography method on IonPac AS11 chromatographic column (Dionex, USA) with a pulsed amperometric detection (IC-PAD) followed by alkaline digestion with tetramethylammonium hydroxide (TMAH) in a closed system and with the assistance of microwaves was developed and used for the comparative analysis of two types of human thyroid samples. Statistical analysis revealed over eightfold reduction of iodine concentration in the pathological tissues (the mean value was 77.13 ± 14.02 ppm) in comparison with the control group (622.62 ± 187.11 ppm for frozen samples and 601.49 ± 192.11 ppm for formalin-fixed ones). A good correspondence (for 10 additional determinations) between the certified (3.38 ± 0.02 ppm with variation coefficient (V.C.) of 0.59% for Standard Reference Material (SRM) NIST 1549-non-fat milk powder) and the measured iodine concentrations (3.52 ± 0.29 ppm; V.C. = 10%) was achieved. It was pointed out that the way of tissue preservation (either in formalin or by freezing) had no significant effect on the iodine determination result ( α = 0.1). Significantly lower iodide content was found in nodular goiter thyroid samples. The applied conditions of digestion, reinforced by the action of microwaves, brought about a decidedly shorter (less than 20 min) sample preparation time. Suitability of the developed IC method was supported by validation results.